1998
DOI: 10.1073/pnas.95.5.2636
|View full text |Cite
|
Sign up to set email alerts
|

Functional disruption in the organization of the brain for reading in dyslexia

Abstract: Learning to read requires an awareness that spoken words can be decomposed into the phonologic constituents that the alphabetic characters represent. Such phonologic awareness is characteristically lacking in dyslexic readers who, therefore, have difficulty mapping the alphabetic characters onto the spoken word. To find the location and extent of the functional disruption in neural systems that underlies this impairment, we used functional magnetic resonance imaging to compare brain activation patterns in dysl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
533
8
20

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 731 publications
(626 citation statements)
references
References 28 publications
59
533
8
20
Order By: Relevance
“…Over the course of years of extensive experience in extracting invariant information from visual word stimuli, perceptual processes are progressively reorganized, but only in those who become skilled readers. Research with dyslexic adults indicates that, among other areas, the VWFA fails to increase its activity in response to word forms [44,45] (Box 3). A basic functional anatomical model of the typical development of this specialization might provide a framework for the investigation and treatment of atypical development, as in the case of developmental dyslexia.…”
Section: V4 V4mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of years of extensive experience in extracting invariant information from visual word stimuli, perceptual processes are progressively reorganized, but only in those who become skilled readers. Research with dyslexic adults indicates that, among other areas, the VWFA fails to increase its activity in response to word forms [44,45] (Box 3). A basic functional anatomical model of the typical development of this specialization might provide a framework for the investigation and treatment of atypical development, as in the case of developmental dyslexia.…”
Section: V4 V4mentioning
confidence: 99%
“…Adults with a history of developmental dyslexia demonstrate a reduced tendency to activate VWFA (see Fig. I), among other regions, in response to visual words and pseudowords as measured by fMRI [44,45] and MEG responses within the first 200 ms [14]. Such differences have not yet been associated with neuropathology in this region, but may instead reflect the absence of a specialization that accrues over the course of years of successful reading experience [55].…”
Section: Box 3 Vwfa In Developmental Dyslexiamentioning
confidence: 99%
“…In the frontal cortex, phonological processing most often has been attributed to the activity in the posterior and dorsal part of the inferior frontal gyrus and along the precentral gyrus (Jobard et al, 2003;Poldrack et al, 1999;Vigneau et al, 2006), and this frontal activity differed between normal and poor readers. Some studies on reading and rhyming in adults found more left inferior frontal activation for those with dyslexia than for controls (Brunswick et al, 1999;Rumsey et al, 1997;Shaywitz et al, 1998), but others reported more activation for controls (GrossGlenn et al, 1991;Paulesu et al, 1996). Also for children the results are rather inconsistent with dyslexia leading to either more (Georgiewa et al, 2002;Temple et al, 2001) or less activation in the inferior frontal gyrus (Bolger et al, 2008b;Booth et al, 2007;Booth et al, 2008;Cao et al, 2006;Georgiewa et al, 1999;Shaywitz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To examine phonological processing, auditory (Booth et al, 2007), visual word (Bolger et al, 2008b;Cao et al, 2006;Hoeft et al, 2006) or letter rhyming tasks (Paulesu et al, 1996;Shaywitz et al, 1998;Temple et al, 2003) have typically been used. In German visual rhyming tasks, rhyming word pairs usually have an increased visual similarity compared to nonrhyming pairs, with the consequence that pure visual matching strategies allow to solve rhyming tasks, without phonological processing.…”
Section: Introductionmentioning
confidence: 99%
“…The heritability was estimated at 50%–70% (de Kovel et al., 2004; Harlaar, Spinath, Dale, & Plomin, 2005; Shaywitz et al., 1998), but only a small proportion of the genetic basis of dyslexia has been uncovered. Linkage studies pointed at nine chromosomal regions (termed DYX1 to 9) and subsequent association studies identified several dyslexia‐related genes within these regions, for example, DYX1C1 , DCDC2 , KIAA0319 , and ROBO1 .…”
Section: Introductionmentioning
confidence: 99%